2022
DOI: 10.3390/ani12080986
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Damaging Behaviours and Health in Laying Hens

Abstract: Since the ban in January 2012 of conventional cages for egg production in the European Union (Council Directive 1999/74/EC), alternative systems such as floor, aviary, free-range, and organic systems have become increasingly common, reaching 50% of housing for hens in 2019. Despite the many advantages associated with non-cage systems, the shift to a housing system where laying hens are kept in larger groups and more complex environments has given rise to new challenges related to management, health, and welfar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 137 publications
0
11
0
Order By: Relevance
“…The scale of egg farming is also gradually expanding. Globally, the public in general is becoming more conscious of the issues around animal welfare and support for the modern free-range model is emerging [ 86 ]. Our results suggest that the level of welfare and economic outcomes of both of the egg-production farm types in China vary widely.…”
Section: Discussionmentioning
confidence: 99%
“…The scale of egg farming is also gradually expanding. Globally, the public in general is becoming more conscious of the issues around animal welfare and support for the modern free-range model is emerging [ 86 ]. Our results suggest that the level of welfare and economic outcomes of both of the egg-production farm types in China vary widely.…”
Section: Discussionmentioning
confidence: 99%
“…The indoor stocking densities under all three systems were below the maximum limit of nine hens per square meter (EU). More space and freedom of movement can reduce stress and fear in laying hens and reduce destructive behaviour, thus reducing mortality in laying hens [ 56 ]. The outdoor activity time of the laying hens in all three systems reached or exceeded 8 h, which is the welfare standard of free-range laying hens stipulated by the Royal Society for the Prevention of Cruelty to Animals (RSPCA) [ 143 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been found that there are benefits associated with improving the welfare of laying hens. For example, giving laying hens greater behavioural opportunities and freedom of movement can reduce their stress and fear, destructive behaviour and, therefore, mortality [ 56 ]. At the same time, environmental enrichment can reduce severe feather pecking and strengthen the immune system of laying hens, thereby reducing losses [ 57 ].…”
Section: Farm Animal Welfarementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is little available information about the effect of toe pecking on mortality, however it is linked with physiological stress and hence reduced welfare [ 33 ]. Toe pecking can be attributed to cannibalism, and complications may be lethal [ 34 ].…”
Section: Discussionmentioning
confidence: 99%